Contextualization of the Sayur Matua Tradition in Regional Language Learning: A Semiotic Analysis of Simalungun Cultural Values - Manik, Fransiska; Sinulingga, Jekmen; Purba, Asriaty R.; Sinaga, Warisman; Herlina (Raja Zulkarnain Education Foundation, 2025)
This study aims to examine the Sayur Matua funeral ceremony in the Batak Simalungun community as a medium for learning cultural values through Charles Sanders Peirce's semiotic approach. The Sayur Matua ceremony is the highest form of respect given to individuals who die in a perfect state, namely after marrying off all their children and having grandchildren. This tradition is full of cultural symbols that function as a reflection of social, spiritual, and moral values. This study employs a descriptive qualitative approach, incorporating observation, interview, and documentation techniques within the community of Gajapokki Village, Simalungun Regency. The analysis was carried out using Peirce's semiotic theory, which distinguishes signs into icons, indices, and symbols. The results of the study identified 14 ritual stages involving 22 cultural symbols, 18 symbolic functions, and 18 symbolic meanings that reflect the value structure in Simalungun society. This article suggests the integration of Sayur Matua in a local wisdom-based learning curriculum to strengthen students' character education, especially in the aspects of responsibility, solidarity, and respect for ancestors. Thus, Sayur Matua not only functions as a sacred tradition but also as a contextual learning resource in shaping the identity and cultural awareness of the younger generation.